The Impact of Organizational DNA on Institutional Excellence: The Mediating Role of Organizational Agility - Al Khasabah, Mohammad Ali Ibrahim (International Review of Management and Marketing, 2025)
The present study examined the effect of organizational DNA in the attainment of institutional excellence (IE) in public universities in southern Jordan. Additionally, it explored the mediation of organizational agility (OA) in the relationship between organizational DNA and IE. The study sample consisted of 236 respondents, and data were analyzed using partial least squares structural equation modeling (PLS-SEM). Analysis results affirmed significant impact of organizational DNA on IE achievement, and significant impact of organizational DNA on OA. Additionally, OA had a statistically significant effect on IE. Also, OA was affirmed as mediator in the relationship between organizational DNA and IE. Other institutions aiming for excellence can benefit from this study as this study demonstrates the leveraging of organizational DNA and OA to achieve a high level of sustainable excellence.